Science and Sentiment: Social Service and Gender at the University of Toronto, 1888-1910 - Burke, Sara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1993)
AbstractBy examining forms of social thought articulated by members of the University of Toronto between 1888 and 1910, this paper argues that the University's first response to urban poverty was shaped by a combination of assumptions derived from British idealism and empiricism. Although many women at Toronto were pursuing a new interest in professional social work, the University's dominant assumptions conveyed the view that social service was the particular responsibility of educated young men, who were believed to be uniquely suited by their gender and class to address the problems of the city. This study maintains that during this period the construction of gender roles in social service segregated the reform activities of men and women on campus, and, by 1910, had the effect of excluding female undergraduates from participating in the creation of University Settlement, the social agency officially sanctioned by their University.